Use of Fecal Occult Blood Test in Hospitalized Patients: Survey of Physicians Practicing in a Large Central Canadian Health Region and Canadian Gastroenterologists - Stephen Ip; AbdulRazaq AH Sokoro; Al Buchel; Debrah Wirtzfeld; Gerald Konrad; Tunji Fatoye; Harminder Singh (Canadian Journal of Gastroenterology)
BACKGROUND: Although the fecal occult blood test (FOBT) was developed for colorectal cancer screening in the outpatient setting, it continues to be used among hospitalized patients. No previous study has evaluated the knowledge, beliefs and attitudes of practicing physicians on the use of FOBT among hospitalized patients and compared practices among physicians with different medical specialty training.